Islamic Education in the Era of Industrial Revolution 4.0 and the Utilization of Digital Technology in the Teaching and Learning Process - Muhammad Faiq Hirzulloh; Tazkia Arifa Annadhif (Jurnal Iqra': Kajian Ilmu Pendidikan)
This study explored how Islamic education proved its existence in the era of the Industrial Revolution 4.0 and how Islamic education adapts by using digital technology in the teaching and learning process. This study adopts a qualitative approach by using a Systematic Literature Review (SLR) as a study method. The SLR approach was chosen because it has several advantages, one of which is the existence of systematic and standardized procedures. In this study, 120 articles were found to be filtered using the PRISMA Model and analyzed more deeply about the existence of Islamic education in the era of the Industrial Revolution 4.0 and adapted by using digital technology in the teaching and learning process. This study shows that the existence of Islamic education is very worthy of appreciation; it is not only interpreted as a transfer of knowledge and transfer of values but also gives birth to human-centred and technology-based creativity and innovation. The existence of Islamic education can also answer society’s need to live a more meaningful life by utilizing technological tools to improve the quality of education, science, technology, and imtaq, as well as the quality of moral and intellectual human resources. Islamic education aligns with the use of digital technology in the learning process by helping students and teachers, as well as the learning process itself, personalized learning or self-study, freedom to choose all learning approaches, project-based learning, and applicable field practice.